The "Begram Ivories": A Successful Case of Restitution of Some Antiquities Stolen from the National Museum of Afghanistan in Kabul. Issue 4 (2nd December 2016) - Simpson, John
Abstract: This article details a successful case of restitution of important antiquities stolen from the National Museum of Afghanistan in Kabul during the Afghan Civil War (1992–94). These items had been excavated by the Délégation Archéologique Française en Afghanistan at the site of Begram during 1937 and 1939 and were allocated to the museum in Kabul when the excavated finds were divided between the National Museum of Afghanistan and the Musée Guimet (Paris). In Kabul, the most important objects were put on permanent display, but they were placed in storage in 1989 when the museum was officially closed and the capital threatened by war after the withdrawal of Soviet forces. Many objects were hidden, and some are now touring in an international exhibition hosted by the British Museum in 2011. 1 However, most of the Begram ivories were stolen and entered different collections. The following article discusses how a group of 20 of these exquisite carvings were acquired, conserved, exhibited, and returned to Kabul as a direct result of the negotiations for the British Museum exhibition. 2 This allowed the first scientific analyses of Indian ivories of this period, and the results provided important new evidence for the extent of polychromy as well as the scale of the different unrecorded conservation treatments previously applied to these highly fragile objects. 3 The objects were returned safely to Kabul in 2012. This article also sets out some of the lessons learned from this chain of events and how it can provide an example for future restitutions.